Learning Style Preferences Of Engineers - Kuan, Ng Mei (2004)
This research is especially useful to training provider as it seeks to propose that engineers have a distinct learning style preference, which can be manipulated by training center in designing suitable training programmes. The learning methodology is also discussed along with the factors that restrict and encourage learning.